2015
DOI: 10.1016/j.tjog.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing trend of hysterectomy in Taiwan: A population-based study, 1997–2010

Abstract: The clinical utilization and primary indications of hysterectomy changed substantially in Taiwan from 1997 to 2010. The continued monitoring of changes in hysterectomy rates will be critical for understanding the appropriate indications for hysterectomy and oophorectomy, the emergence of alternative managements for uterine disorders, and future trends in women's reproductive health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…Similar exclusion criteria were applied for establishing the comparison group, which was randomly selected from women without the history of hysterectomy and oophorectomy, with a sample size 4-fold of the case group, frequency matched by the year of birth and the year of surgery. The validity of hysterectomy and hyperlipidemia in the claims data of NHIRD has been reported in previous reports 5 7 .
Figure 1 The flow chart for identifying study cohorts from the National Health Insurance Research Database.
…”
Section: Methodssupporting
confidence: 55%
See 2 more Smart Citations
“…Similar exclusion criteria were applied for establishing the comparison group, which was randomly selected from women without the history of hysterectomy and oophorectomy, with a sample size 4-fold of the case group, frequency matched by the year of birth and the year of surgery. The validity of hysterectomy and hyperlipidemia in the claims data of NHIRD has been reported in previous reports 5 7 .
Figure 1 The flow chart for identifying study cohorts from the National Health Insurance Research Database.
…”
Section: Methodssupporting
confidence: 55%
“…We established a hysterectomy related case group, including women who had received only a hysterectomy, both a hysterectomy and an oophorectomy, and only an oophorectomy from 2000 to 2013. Cases were defined by the procedure codes of 65.5, 65.6, 68.3–5, 68.9 7 and diagnoses codes of uterine myoma (ICD9 code: 218.9), adenomyosis (ICD9 code: 617.0), uterine prolapse (ICD9 code: 618), and ovarian tumor ICD9 code: 220. Women who had been diagnosed with hyperlipidemia (ICD9 code: 272) and/or cancer at baseline, or with cancer within 1 year after hysterectomy were excluded (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LHs have increased worldwide because of less postoperative pain, shorter hospital length of stay, and faster recovery [3]. Previous studies in the United States [1], Austria [4], the Netherlands [5], Italy [6], and Taiwan [2,7,8] showed an increase in laparoscopic techniques and a decrease in total abdominal hysterectomy (TAH) and VH. Huang et al [7] reported an increase in subtotal abdominal hysterectomy (SAH).…”
mentioning
confidence: 99%
“…Logically, the CUSUM learning curve analysis of in-hospital complication rates would nd fewer procedures required than analysis of surgical recurrence found and more procedures than operation time did. The other limitation is that hysterectomy volumes fell in Taiwan during our follow-up period 23 . This caused a signi cant difference in the rates of previous and concurrent hysterectomy in surgeon A's cohort.…”
Section: Discussionmentioning
confidence: 94%